Edukimia Vol 2 No 3 - Juli 2020 - Editorial - Front Cover, TOC, Editorial - Tim Editorial Edukimia (Universitas Negeri Padang, 2020)
Front cover, Table of Contents (TOC) and Editorial for Edukimia Volume 02, Issue 03.